Growth in Local Tax Burdens - Gottlieb, L. R. (Quarterly Journal of Economics, 1923)
Journal Article Growth in Local Tax Burdens Get access L. R. Gottlieb L. R. Gottlieb School of Commerce, Accounts, and Finance, New York University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 37, Issue 2, February 1923, Pages 374–382, https://doi.org/10.2307/1883937 Published: 01 February 1923